Osteochondral tissue engineering: challenges, current strategies, and technological advances - Oliveira, Joaquim M. (2018)
In the last few years, osteochondral tissue engineering has shown an increasing development in advanced tools and technologies for damaged underlying subchondral bone and cartilage tissue repair and regeneration. Considering the limitation of articular cartilage to heal and self-repair, new therapeutic options are essential to develop approaches based on suitable strategies made of appropriate engineered biomaterials. This book overviews the most recent developments in the field of osteochondral tissue engineering. It covers the concepts and current challenges for bone and cartilage repair and regeneration, along with technological advances for osteochondral tissue. Specific topics include viscosupplementation, tissue engineering approaches, technological advances with stem cells and cell-based therapies with applications for osteochondral, bioreactors and microfluidics including multi-chamber bioreactors, and in vitro and in vivo mimetic models. This book presents challenges and strategies being developed that face not only bone and cartilage regeneration, but also establish the osteochondral interface formation in order to translate it into a clinical setting. Each chapter is prepared by world know expert on their field, and serves as a core reference for biomedical engineering students and a wide range of established researchers and professionals working in the orthopedic field.